Welcome to Scribd, the world's digital library. Read, publish, and share books and documents. See more ➡
Standard view
Full view
of .
×
0 of .
Results for:
P. 1
Integration

# Integration

Ratings: (0)|Views: 3,857|Likes:
MATH131 - lecture notes
MATH131 - lecture notes

### Availability:

See More
See less

12/15/2012

pdf

text

original

Integration
1 Antiderivatives
Consider the function
(
x
) = 3
x
2
. Suppose that instead of ﬁnding the derivative of
we wishto ﬁnd a function
, which when diﬀerentiated yields
, i.e. we seek a function
such that
(
x
) = 3
x
2
.It is fairly easy to see that
(
x
) =
x
3
will do. We shall then say that
is an
antiderivative
of
.
Antiderivative
Deﬁnition 1.1
If
is a given function, then
is an antiderivative of
provided that
(
x
) =
(
x
)
.
Note that we have said “an antiderivativenot “the antiderivative”. The reason is that afunction may have many antiderivatives. For example consider again
(
x
) = 3
x
2
. We haveseen that
(
x
) =
x
3
is one antiderivative, since
(
x
) =
(
x
). Equally well, so are
G
(
x
) =
x
3
+ 1
,
(
x
) =
x
3
1726739etc., since they also give 3
x
2
when diﬀerentiated. Indeed it is plain that
(
x
) =
x
3
+
where
is any constant is an antiderivative of
.
Theorem 1.2
If
(
x
)
is an antiderivative of
(
x
)
, then so is
(
x
)+
, for any constant
.
Proof
. We know
(
x
) =
(
x
). Then
ddx
[
(
x
) +
] =
ddx
(
x
) +
ddx
=
(
x
) + 0 =
(
x
)
.
Example 1.1
Find antiderivatives for:(a)
4
x
3
(b)
x
2
+ 1
(c)
x
4
+
x
3
+
x
(d)
3sin3
x
.
Solution
We must ﬁnd functions which when diﬀerentiated yield the above.(a) It is fairly obvious that
x
4
+
will do for any constant
.(b) It is not hard to see that
x
3
/
3 +
x
+
will suﬃce.(c) Again we take
x
5
/
5 +
x
4
/
4 +
x
2
/
2 +
.(d) Clearly
cos3
x
+
will do.
We have seen that any function
(
x
) =
x
3
+
is an antiderivative of 3
x
2
. Now we areentitled to ask, “Are there any more antiderivatives?” Could there be some other strangefunction, not of the form
(
x
) =
x
3
+
, which when diﬀerentiated also gives 3
x
2
?The answer is that there is not. A rigorous proof of this depends on the following tworesults, the ﬁrst of which we shall not prove here, as it would take us too far aﬁeld.1

Rolle’s Theorem
Theorem 1.3 (Rolle’s Theorem)
. Suppose
a < b
and
is continuous on
[
a,b
]
and diﬀer-entiable on
(
a,b
)
and that
(
a
) =
(
b
)
. Then there exists a point
ξ
(
a,b
)
such that
(
ξ
) = 0
.
This has a very simple geometric interpretation........................
aξb
.....................
(
x
)Figure 1.1The Theorem says that in Figure 1.1, there must exist a point
ξ
, at which there is a horizontaltangent to the graph of
.
Mean Value Theorem
Theorem 1.4 (Mean Value Theorem)
Suppose
a < b
and
is continuous on
[
a,b
]
and diﬀerentiable on
(
a,b
)
. Then there exists a point
ξ
(
a,b
)
such that
(
b
)
(
a
)
b
a
=
(
ξ
)
.
(1)
Proof
. Let
g
(
x
) =
(
x
)
(
a
)
(
b
)
(
a
)
b
a
(
x
a
)
.
Then
g
(
a
) =
g
(
b
) = 0. Thus
g
satisﬁes then conditions of Rolle’s Theorem. Hence there existsa point
ξ
at which
g
(
ξ
) = 0, i.e.0 =
(
ξ
)
(
b
)
(
a
)
b
a.
The geometrical interpretation of this is as follows....................................................................................................................................................................................
(
b
)
(
a
)
aξbRQ
Figure 1.22

Let
and
Q
be the points (
a,
(
a
)) and (
b,
(
b
)) as shown in Figure 1.2 and let
R
be the point(
b,
(
a
)). Then
QR
=
(
b
)
(
a
) and
PR
=
b
a
. Hence the left hand-side of (1) is just
QR/PR
which is the slope of
PQ
.On the other hand,
(
ξ
) is the slope of the tangent at
ξ
.What the theorem says is that there is at least one point
ξ
, at which the tangent is parallelto the chord
PQ
.An immediate consequence of this is the following result.
Theorem 1.5
If
(
x
)
0
then
(
x
)
constant
.
Proof
. Let
a
and
b
be any two distinct points. We shall show that
(
a
) =
(
b
), which meansthat the value of
is the same at any two points, i.e.
is a constant function.For convenience, suppose
a < b
. Then for some
ξ
(
a,b
)
(
b
)
(
a
)
b
a
=
(
ξ
)
.
But the right-hand side is zero by hypothesis, and so
(
a
) =
(
b
).This result can be used to prove the following theorem.
Theorem 1.6
If
1
and
2
are antiderivatives of
then
1
(
x
)
2
(
x
)
constant
.
Proof
. We have
1
(
x
) =
(
x
) and
2
(
x
) =
(
x
). Hence(
1
2
)
(
x
) =
(
x
)
(
x
) = 0
.
Then by Theorem 1.5,
1
(
x
)
2
(
x
)
constant
.
What this theorem says is that once we have found one antiderivative, then all others diﬀerfrom that one only by a constant. Thus returning to
(
x
) = 3
x
2
, we know
(
x
) =
x
3
is anantiderivative. Then by Theorem 1.2, so is
x
3
+
, and by Theorem 1.6 there are no others.
Indeﬁnite Integral
We now introduce some special notation. If
is an antiderivative of
we write

(
x
)
dx
=
(
x
) +
(2)and say that

(
x
)
dx
is the
indeﬁnite integral
of
with respect to
x
, or often more simplythe
integral
of
. The reason for this symbolization will become clear later.It follows that
(
x
) =
(
x
), i.e.
ddx

(
x
)
dx
=
(
x
)
,
(3)and

(
x
)
dx
=
(
x
) +
C.
3

## Activity (43)

### Showing

AllMost RecentReviewsAll NotesLikes